Development of SIAKAD Applications in Balikpapan Schools using APXP: Advanced Personal Extreme Programming - Aidil Saputra Kirsan; Nursanti Novi Arisa; Vika Fitratunnany Insanittaqwa (Jurnal Inovtek Polbeng Seri Informatika, 2022)
The iteration process in Personal Extreme Programming (PXP) consists of Initialization, Design, Implementation, Testing, and Retrospective. There are still areas for improvement in this method. In the future, this method will be a problem because it can make the application unable to run after the retrospective process. One of the problems is the version update app on Android. We propose an Advanced PXP model (APXP) for an academic information system (SIAKAD) in Balikpapan Schools that contains PXP modifications at the beginning and end of the process. At the middle stage of APXP is system testing. Each process from 1-11 iterations produces Valid results. We add Deployment methods such as Blue-Green Deployment Strategy. The deployment process can change very quickly once the switch service changes in the APXP method. Furthermore, the deployment process has almost no issues with different versions of the service